A fine scale eco-epidemiological study on endemic visceral leishmaniasis in north ethiopian villages - Kirstein, Oscar David; Skrip, Laura; Abassi, Ibrahim; Iungman, Tamara; Horwitz, Ben Zion; Gebresilassie, Araya; Spitzova, Tatiana; Waitz, Yoni; Gebre-Michael, Teshome; Volf, Petr; Hailu, Asrat; Warburg, Alon (Acta tropica, 2018)
Visceral Leishmaniasis (VL) is a disseminated protozoan infection caused by Leishmania donovani that affects almost half a million people annually. In Northern Ethiopia, VL is common in migrant agricultural laborers returning from the lowland sesame fields of Metema and Humera. Recent VL foci have emerged in resident rural populations near the town. In the current study, we evaluate multilevel entomological, epidemiological and ecological factors associated with infection and disease through fine-scale eco-epidemiological analyses in three villages. Satellite images showed that villages constructed in or close to vertisols, were likely to become endemic for VL. Vertisols or black-cotton soil, are characterized by high contents of smectitic clay minerals, which swell when hydrated and shrink upon desiccation, causing extensive deep cracking during the dry season. The population densities of Phlebotomus orientalis, the vector, were negatively correlated with distance from vertisols and persons living close to vertisols were more likely to be bitten by sand flies, as evidenced by sero-positivity to Ph. orientalis saliva. Apparent (albeit non-significant) clustering of VL cases and abundant asymptomatic infections close to vertisols, suggest anthroponotic transmission around houses located close to vertisols. Comparable rates of male and female volunteers, mostly under 15 years of age, were infected with L. donovani but a significantly higher proportion of males succumbed to VL indicating a physiological gender-linked male susceptibility. Our data suggest that the abundant infected persons with high parasitemias who remain asymptomatic, may serve as reservoir hosts for anthroponotic transmission inside villages. Only limited insights on the transmission dynamics of L. donovani were gained by the study of environmental factors such as presence of animals, house structure and vegetation cover.
Keywords: Agriculture; Psychodidae; Epidemiologic Studies; Male; Rural Population; Etiopie; Ecosystem; Leishmaniasis, Visceral; Occupational Diseases; Adolescent; Cohort study; Child; Ethiopia; nemoci z povolání; dítě; Adult; venkovské obyvatelstvo; rozložení podle pohlaví; leishmanióza viscerální; dospělí; epidemiologické studie; mužské pohlaví; Population Density; Sex Distribution; Soil; Visceral leishmaniasis; mladiství; zemědělství; Animals; lidé; ženské pohlaví; Leishmania donovani; roční období; Seasons; Humans; Phlebotomine sand flies; zvířata; Ecoepidemiology; ekosystém; Vertisols; půda; Female; hustota populace